2019
DOI: 10.1007/s11120-019-00675-0
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II core quenching in desiccated Leptolyngbya ohadii

Abstract: Cyanobacteria living in the harsh environment of the desert have to protect themselves against high light intensity and prevent photodamage. These cyanobacteria are in a desiccated state during the largest part of the day when both temperature and light intensity are high. In the desiccated state, their photosynthetic activity is stopped, whereas upon rehydration the ability to perform photosynthesis is regained. Earlier reports indicate that light-induced excitations in Leptolyngbya ohadii are heavily quenche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While the cytochrome b6f complex had been proposed as the redox sensor, a recent work had shown that it is not involved in cyanobacterial state transition ( Calzadi et al, 2019 ). In the cyanobacterial species, S ynechococcus elongatus and Synechocystis sp PCC 6803, there is no redistribution of PBS, nor is there any spillover from PSII to PSI ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ). However, in order to balance the excitation pressure between PSII and PSI, in state II, the PSII-core and not the PBS is quenched ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ).…”
Section: Regulation Of Energy Transfer and Trapping In The Photosynth...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the cytochrome b6f complex had been proposed as the redox sensor, a recent work had shown that it is not involved in cyanobacterial state transition ( Calzadi et al, 2019 ). In the cyanobacterial species, S ynechococcus elongatus and Synechocystis sp PCC 6803, there is no redistribution of PBS, nor is there any spillover from PSII to PSI ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ). However, in order to balance the excitation pressure between PSII and PSI, in state II, the PSII-core and not the PBS is quenched ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ).…”
Section: Regulation Of Energy Transfer and Trapping In The Photosynth...mentioning
confidence: 99%
“…In the cyanobacterial species, S ynechococcus elongatus and Synechocystis sp PCC 6803, there is no redistribution of PBS, nor is there any spillover from PSII to PSI ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ). However, in order to balance the excitation pressure between PSII and PSI, in state II, the PSII-core and not the PBS is quenched ( Bhatti et al, 2020 ; Ranjbar Choubeh et al, 2020 ). Furthermore, in S. elongatus , two (sub) populations of PSII, namely quenched and unquenched exist, in both states I and II.…”
Section: Regulation Of Energy Transfer and Trapping In The Photosynth...mentioning
confidence: 99%